2010
DOI: 10.1111/j.1467-8624.2010.01502.x
|View full text |Cite
|
Sign up to set email alerts
|

Development in Children’s Comprehension of Linguistic Register

Abstract: For socially appropriate communication, speakers must command a variety of linguistic styles, or registers, that vary according to social context and social relationships. This study examined preschool children's ability to use a speaker's register choice to infer the identity of their addressee. Four-year-olds could draw correct inferences based on Spanish and formal speech, and had limited success with infant-directed and casual styles. Five-year-olds drew appropriate inferences with all 4 styles; moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 32 publications
1
38
1
Order By: Relevance
“…In early infancy, children are already able to process environmental regularities, both in linguistic input (Tomasello, 2003) and social roles including gender-typed roles (Eichstedt et al, 2002; Poulin-Dubois et al, 2002; Serbin et al, 2002; Martin and Ruble, 2004; Hill and Flom, 2007). During their preschool years, children become increasingly aware that language variation predicts variation in a range of social groups and can map linguistic information onto social categories (Hirschfeld and Gelman, 1997) including regional dialects (Wagner et al, 2014) and speech styles (Wagner et al, 2010); namely, they become capable of relating different ways of speaking with different categories of speakers and contexts of speech with increasing accuracy. They are also able to adjust their linguistic behavior to social situations (Patterson, 1992; Roberts, 1997; Díaz-Campos, 2005; Smith et al, 2007) and to the social roles they enact in pretend play for instance (Corsaro, 1979; Andersen, 1990; Ervin-Tripp, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In early infancy, children are already able to process environmental regularities, both in linguistic input (Tomasello, 2003) and social roles including gender-typed roles (Eichstedt et al, 2002; Poulin-Dubois et al, 2002; Serbin et al, 2002; Martin and Ruble, 2004; Hill and Flom, 2007). During their preschool years, children become increasingly aware that language variation predicts variation in a range of social groups and can map linguistic information onto social categories (Hirschfeld and Gelman, 1997) including regional dialects (Wagner et al, 2014) and speech styles (Wagner et al, 2010); namely, they become capable of relating different ways of speaking with different categories of speakers and contexts of speech with increasing accuracy. They are also able to adjust their linguistic behavior to social situations (Patterson, 1992; Roberts, 1997; Díaz-Campos, 2005; Smith et al, 2007) and to the social roles they enact in pretend play for instance (Corsaro, 1979; Andersen, 1990; Ervin-Tripp, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, other research suggests that young children confound “national group” with “linguistic group” and see language as a basis by which national groups are formed (Carrington & Short, 1995; Jahoda, 1964). Related to this possibility, preschool-aged children match voices in their native language with pictures of individual speakers who are of a familiar race, wear familiar clothes, and live in familiar dwellings (Hirschfeld & Gelman, 1997; Wagner, Greene-Havas, & Gillespie, 2010). Finally, language exposure influences children’s national group identification.…”
Section: Development Of Language-based Social Evaluationmentioning
confidence: 99%
“…For example, children associate speech in a language they do not know with unfamiliar clothing and housing styles, suggesting that speakers of such a language are in the child's out-group (Hirschfeld & Gelman, 1997). Moreover, recent work has shown that children can draw appropriate social inferences about the identity of a speaker's addressee as a function of the speech style being spoken (formal, casual, infant-directed;Wagner, Greene-Havas, & Gillespie, 2010). Beyond this general knowledge that language marks social information, children also show a strong social preference for speakers of their native language from very early in development.…”
mentioning
confidence: 96%